Pembelajaran Menganalisis Isi, Struktur, dan Kebahasaan Teks Negosiasi Menggunakan Media Komik Digital di Kelas X SMA Pasundan 1 Bandung - Rizki Arya Muhamad; Titin Nurhayatin; Marlia Marlia (ENGGANG: Jurnal Pendidikan, Bahasa, Sastra, Seni, dan Budaya, 2024)
This study aims to describe: (1) the author's ability in planning, implementing, and disseminating learning of negotiation text analysis using digital comics in Class X of SMA Pasundan 1 Bandung; (2) the condition of learning analysis of negotiation text in Class X of SMA Pasundan 1 Bandung before using digital comics; (3) the condition of learning after using digital comics as a learning medium; (4) the difference in the ability to write explanatory text between the experimental and control classes after using digital comics. The approach used was quantitative with a pure experimental method and a pretest-posttest control group design. The results of the study showed: (1) the author succeeded in planning, implementing, and starting learning with a score of 3.9 in planning and implementation, both in the very good category; (2) the pretest score of students in the experimental class before using digital comics was still below the minimum completion criteria, with an average of 20; (3) after using digital comics, the posttest score of the experimental class reached an average of 77 and met the minimum completion criteria; (4) The experimental class showed higher scores than the control class, as proven by the results of the pretest-posttest and independent sample t-test (Sig. value = 0.001 < 0.05).